Patient satisfaction about the primary health care services in Anbar province, Iraq (Journal of Ideas in Health, 2024)
Background: Patient satisfaction determines care alignment with expectations, encompassing availability, cost, and environment, crucial for service quality. This study aims to investigate key determinants influencing patient satisfaction with Primary Health Care Centers (PHCC) in Anbar province, Iraq. Methods: A cross-sectional study was carried from 15th November 2022 till 16th March 2023 across six PHCC using multistage sampling technique. Semi-structured questionnaire was recruited to interview patients. Descriptive and bivariate and multiple logistic regression analyses were conducted to identify significant factors affecting patients’ satisfaction toward PHCC.Results: A total of 300 patients were included with mean age of 35.7 (+ 4.2), ranged 15-69 years. The PHCC attained an overall satisfaction rate of 64.7%. Patients voiced discontent primarily with waiting times for consultation (67.3%) and appointment scheduling (60.7%). However, 69.3% were content with the proximity to the PHCC. Doctors' conduct was praised by 82.0% of respondents, yet 56.7% noted a lack of health education programs. Management was appreciated by 70.0%, yet laboratory services were received by only 57.7%. Moreover, 75.0% reported essential drug unavailability, and 54.7% mentioned a lack of medical instruments. Factors associated with patients’ satisfaction were aged less than 40 years old (OR = 3.54, 95% CI: 2.44 to 5.21), being male (OR = 3.76, 95% CI: 2.68 to 6.15), unmarried (OR = 4.01, 95% CI: 3.06 to 8.4) and low educated OR = 2.77, 95% CI: 2.76 to 7.57).Conclusion: Patients' satisfaction with PHCC is notably linked to proximity, respectful doctor behavior, privacy during examinations, and efficient management. Dissatisfaction arises from appointment scheduling, follow-up, and the unavailability of health education, instruments, and drugs.